Overexpression of Long Non-Coding RNA Linc01315 Predicts Poor Prognosis in Breast Cancer - Xue, Jingyan; Huang, Sheng; Chen, Jiaying; Chen, Yi-zuo; Shao, Zhi-min; Wu, Jiong; Chi, Yayun (Frontiers in Oncology, 2021)
Background: LncRNAs have been demonstrated to have critical roles in regulating cancer cell proliferation, survival and sensitivity to therapy. The potential application of using LncRNAs to predict prognosis and therapeutic response to cancer treatment holds high promise, but lncRNAs with predictive value remain to be identified and underlying mechanisms have not been completely understood. Methods: Expression of Linc01315 was detected in 282 breast cancer tissues by quantitative reverse-transcription polymerase chain reaction (qRT-PCR). We analyzed the relationship between Linc01315 expression level and clinic pathological features of breast cancer patients. Multiple regression analysis was used to evaluate Linc01315 predictive value of patients’ prognosis. Results: Our study revealed that Linc01315 expression level was significantly correlated with vessel invasion (p = 0.028) and tumor subtype (p = 0.039). The Kaplan–Meier survival curves indicated that patients with lower Linc01315 expression level had significantly longer disease free survival (DFS) (P = 0.002) and overall survival (OS) (P=0.019). Multiple regression analysis showed that Linc01315 level could be an independent predictive factor for DFS (hazards ratio = 0.613, 95% confidence interval = 0.375-1.003; P = 0.049) and OS (hazards ratio = 0.439, 95% confidence interval = 0.228-0.845; P = 0.014). Further analysis showed that low Linc01315 level patients with endocrine therapy could benefit patients DFS (P=0.037) and OS (P=0.025). Conclusion: Our results demonstrate that Linc01315 expression level is significantly correlated with breast cancer patients prognosis. Linc01315 may represent an independent prognostic marker and therapeutic target in breast cancer.